2022
DOI: 10.1007/s10522-022-09956-z
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng volatile oil prolongs the lifespan and healthspan of Caenorhabditis elegans

Abstract: Ginseng volatile oil (GVO) is one of the main components of ginseng and has antibacterial and anti-inflammatory properties. In this study, gas chromatography–mass spectrometry (GC–MS) was applied to characterize GVO chemical composition, and 73 volatile components were detected from GVO. Caenorhabditis elegans was used as animal model to further elucidate the antioxidant and anti-aging effects of GVO in vivo. The results suggested that GVO significantly prolonged the lifespan of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…A similar effect was not observed in H. neglectum treatment group probably due to the presence of other impurities that might have acted as antagonist for the bioactive function of mangiferin. Our ndings on the effect of P. ginseng on IAM accumulation are consistent with current available literature [34][35][36] . Ginsenoside, a bioactive component of P. ginseng has been reported to extend lifespan and reduce IAM accumulation via the modulation of lipid metabolism and activation of the stress response biomolecules 34 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar effect was not observed in H. neglectum treatment group probably due to the presence of other impurities that might have acted as antagonist for the bioactive function of mangiferin. Our ndings on the effect of P. ginseng on IAM accumulation are consistent with current available literature [34][35][36] . Ginsenoside, a bioactive component of P. ginseng has been reported to extend lifespan and reduce IAM accumulation via the modulation of lipid metabolism and activation of the stress response biomolecules 34 .…”
Section: Discussionsupporting
confidence: 92%
“…Gingko biloba has been reported to prevent mitochondrial dysfunction through the suppression of caspase-9 activation, mitochondrial ROS generation as well as the expression of toll-like receptors thereby mitigating cell necrosis [31][32][33] . Similarly, various extracts of ginseng have been reported to sustain healthy aging and lifespan in C. elegans [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…And research has found that when GSEs are cooked, the lower polarity of ginsenosides, total phenols, total flavonoids, their antioxidant capacity, and antiinflammatory effects all increase with increasing cooking time [40].Ginseng volatile oil (GVO) is one of the main components of P. ginseng. Research has found that ginseng volatile oil can delay the aging of the elegans elegans by activating autophagy and antioxidant effects [41].…”
Section: Other Compoundsmentioning
confidence: 99%
“…This places a considerable burden on the healthcare system and threatens economic development. Drugs such as aspirin and metformin can delay aging but long‐term intake can cause adverse reactions such as anti‐platelet aggregation, diarrhea, nausea, and abdominal pain 2 . A safe and effective anti‐aging strategy is therefore urgently required.…”
Section: Introductionmentioning
confidence: 99%